Relationship between food ingestion, body mass index and physical activity level of elderly people with ages 60 to 70 years of age happy extension project of the faculty of science in biomedical Cacoal / RO - FACIMED - Moura, Samantha Almeida de (2012)
Objective: The objective of this research was to analyze the correlation between the level of physical activity, caloric intake and BMI (Body Mass Index) of elderly people aged 60 to 70 years of Project Extended Happy Age practitioners of physical activities in school gym FACIMED. Substances and Methods: To investigate the food intake through a questionnaire of habitual food days, assessing the level of physical activity through the International Physical Activity Questionnaire (IPAQ) and the IMC of identifying evaluated. The research involved 28 subjects with mean age of 66, 86 ± 2.42 for the female group and 68.00 ± 1.41 for the male group. To select the sample, we used the technique of convenience, and the nature of correlational research. The measures used to collect data were the weight, height, body mass index (IMC), the International Physical Activity Questionnaire (IPAQ) and a 24-hour food recall. Results: The data show that the assessment of IMC elderly surveyed are at overweight, all are considered active by IPAQ and have an average energy intake of 1340.27 and 1182.62 for the female to male. Having significance in the relationship between all variables studied, but most evident between caloric intake and BMI. Conclusion: Therefore the greater the caloric intake of food the higher the body mass index of evaluated.